In Vitro Selection of Local Maize (Zea mays) on NaCl Stress and Its Genetic Characterization using RAPD - Triono Bagus Saputro; Fathin Finariyah; Siti Dianawati; Nur Fadlilatus Sholihah; Dini Ermavitalini (Biosaintifika: Journal of Biology & Biology Education, 2016)
Maize (Zea mays) is one of graminae plants that widely spread for many purposes wheter in food industry, feed, or bioenergy. Those high utilization required an increment in production, but unfortunately the needs were not meet to the demands since conversion of agricultural area increase lately. Indonesia has 99.093 km of shoreline that recognize as marginal land where the salinity is high as well. This research try to obtain tolerant variant from two local cultivars that planted in Madura Island. Manding and Talango varieties were used as an explant for callus induction stage in MS supplemented with 2.4 D. The result show that 4 ppm of 2.4 D were the best concentration to induce the callus in both varieties. The induced callus were exposed to medium MS that contain NaCl (0, 2500, 5000, and 7500 ppm). In 7500 ppm of NaCl, Manding variety has 100% of surviving callus, while Talango variety only 66.7%. Furthermore, Manding variety shows a better performance in callus weight improvement with 170 mg, while Talango shows no improvement of callus weight. The result of RAPD analysis indicate that the genome characteristic were different between initial callus and surviving callus. Out of ten primers, only five primers shows polymorphism i.e OPA 13, OPB 07, OPC 02, OPK 20, and OPU 19. Manding can be further developed as high tolerance variety in Salinity stress, thus it proposed to be developed furthermore.How to CiteSaputro, T. B., Finariyah, F., Dianawati, S., Sholihah, N. F., Ermavitalini, D. (2016). In Vitro Selection of Local Maize (Zea mays) on NaCl Stress and Its Genetic Characterization using RAPD. Biosaintifika: Journal of Biology Biology Education, 8(3), 344-352.